Comparison of trunk mechanics and spatiotemporal outcomes in caregivers using a robotic assisted transfer device and a mobile floor lift. (2nd January 2023) - Greenhalgh, Mark; Blaauw, Eline R.; Crytzer, Theresa; Deepak, Nikitha; Grindle, Garrett G.; Koontz, Alicia M.; Cooper, Rory A.
Abstract : Objective: The purpose of this study was to compare trunk mechanics, distance covered, and average instantaneous velocity and acceleration recorded with caregivers performing transfer tasks using a research mannequin with both a prototype robotic assisted transfer device (RATD) and a mobile floor lift. Design: Cross-Sectional. Setting: Biomechanics Lab and Human Engineering Research Laboratories. Participants: Caregivers ( N = 21). Intervention: Robotic Assisted Transfer Device. Outcome Measures: Range of flexion-extension, lateral bend, and axial rotation; distance covered; average instantaneous velocity and acceleration. Results: Caregivers performing transfers using the RATD as compared to when using the moble floor lift reported significantly smaller range of trunk flexion-extension, lateral bending, and axial rotation, and reported lower pelvic based distance covered and slower average instantaneous velocity and acceleration (P < 0.001). Conclusion: The design and usability of a RATD indicates design driven mobility advantages over clinical standard mobile floor lifts due to its ability to expand the workspace while further reducing risk factors for low back pain. While the concept is promising, further testing is required to address limitations and confirm the concept for clinical applications.